Using implementation mapping to develop strategies for preventing non-communicable diseases in Japanese small- and medium-sized enterprises - Miyuki Odawara; Junko Saito; Akiko Yaguchi-Saito; Maiko Fujimori; Maiko Fujimori; Yosuke Uchitomi; Yosuke Uchitomi; Yosuke Uchitomi; Taichi Shimazu (Frontiers Media S.A., 2022)
IntroductionWorkplace programs to prevent non-communicable diseases (NCDs) in the workplace can help prevent the incidence of chronic diseases among employees, provide health benefits, and reduce the risk of financial loss. Nevertheless, these programs are not fully implemented, particularly in small- and medium-sized enterprises (SMEs). The purpose of this study was to develop implementation strategies for health promotion activities to prevent NCDs in Japanese SMEs using Implementation Mapping (IM) to present the process in a systematic, transparent, and replicable manner.MethodsQualitative methods using interviews and focus group discussions with 15 SMEs and 20 public health nurses were conducted in a previous study. This study applied the Consolidated Framework for Implementation Research and IM to analyze this dataset to develop implementation strategies suitable for SMEs in Japan.ResultsIn task 2 of the IM, we identified performance objectives, determinants, and change objectives for each implementation stage: adoption, implementation, and maintenance; to identify the required actors and actions necessary to enhance implementation effectiveness. Twenty-two performance objectives were identified in each implementation stage. In task 3 of the IM, the planning group matched behavioral change methods (e.g., modeling and setting of graded tasks, framing, self-re-evaluation, and environmental re-evaluation) with determinants to address the performance objectives. We used a consolidated framework for implementation research to select the optimal behavioral change technique for performance objectives and determinants and designed a practical application. The planning team agreed on the inclusion of sixteen strategies from the final strategies list compiled and presented to it for consensus, for the overall implementation plan design.DiscussionThis paper provides the implementation strategies for NCDs prevention for SMEs in Japan following an IM protocol. Although the identified implementation strategies might not be generalizable to all SMEs planning implementation of health promotion activities, because they were tailored to contextual factors identified in a formative research. However, identified performance objectives and implementation strategies can help direct the next steps in launching preventive programs against NCDs in SMEs.